Adjuvant Application of Shenmai Injection for Sepsis: A Systematic Review and Meta-Analysis. (9th August 2022) - Sun, Ye; Liu, Yilin; Li, Li; Xue, Bing; Cao, Yan
Abstract : Objective . To compare the efficacy and safety of Shenmai injection plus regular treatment versus regular treatment alone in the treatment of sepsis. Methods . Review Manager 5.3 was used. Databases including PubMed, Cochrane Library, Wan-FANG, VIP, CNKI, and CBM were searched for the relative control and randomized studies till June 2022. Primary outcomes were 28-day mortality; case fatality rate; APACHE II score; and levels of procalcitonin, tumor necrosis factor- α, interleukin-6, and C-reaction protein. Secondary outcomes were measurements related to inflammatory reactions, coagulation function, immune function, and organ function. Results . In total 21 studies with 1469 patients were included. Shenmai injection plus regular treatment of sepsis significantly decreased 28-day mortality rate (odds ratio: 0.36 (0.20, 0.63); p = 0.0004 ) and case fatality rate (odds ratio: 0.32 (0.19, 0.54), p < 0.0001 ) and significantly further reduced APACHE II score (standard mean deviation: −1.14 (−1.30, 0.99); p < 0.00001 ). Procalcitonin reduction was similar in the two groups (standard mean deviation: −0.59 (−1.64, 0.46); p = 0.27 ). Tumor necrosis factor- α (standard mean deviation: −1.96 (−2.79, −1.13); p < 0.00001 ), interleukin-6 (standard mean deviation: −1.52 (−2.13, −0.91); p < 0.00001 ), and C-reaction protein (standard mean deviation: −2.37 (−4.26, −0.49); p = 0.01 ) levels were significantly further decreased in the Shenmai injection group. Most of the measurements related to inflammatory reaction, coagulation function, immune function, and organ function were significantly regulated in the Shenmai injection group. Furthermore, there was no adverse event, and two study groups had similar adverse event rates. Conclusion . Shenmai injection as adjuvant therapy shall be effective and safe in the treatment of sepsis. However, further investigation is still warranted especially regarding safety. Adjuvant application of Shenmai injection in sepsis is worth further investigation.